Bewertung der freien Schilddrüsenhormone (FT4 und FT3) in der Schilddrüsen- Funktionsroutinediagnostik - Passath, A; Leb, G.; Goebel, R. (Nuklearmedizin - NuclearMedicine, 1985)
The validity of the free thyroid hormone parameters (FT4 and FT3) was verified in a random sample of 154 ambulatory patients with thyroid conditions. The “euthyroid range” of FT4 was between 15.67 and 30.66 pmol/1; median 21.98 pmol/1. The distribution of the FT4 readings peaked on the left and sloped to the right (log normal). In our laboratory, the “euthyroid reference range” of FT4 is between 10-28 pmol/1. The “euthyroid range” of FT3 extended from 4.6 to 9.7 pmol/ 1; median 6.63 pmol/1. The distribution of the readings was likewise log normal. The values of FT4 and FT3 are not significantly influenced by TBG concentration anomalies in otherwise healthy thyroid patients. For purposes of discrimination between euthyroidism and hyperthyroidism, FT3 (95%) and FT4 (90%) are better suited than the corresponding quotients for the free hormone fraction or the total hormone concentrations. On the other hand, the free hormone parameters are less suitable for the diagnosis of hypothyroidism. These results were deduced theoretically from mathematical function analyses between the TBG-independent free hormone parameters and the TBG-dependent hormone concentrations.